Improving Mental Health in Prisons Through Biophilic Design - Söderlund, J.; Newman, Peter (2017)
Increasing nature and natural elements within a prison offers the potential to destress residents, improve mental health, cognitive functioning and learning; reduce recidivism and increase receptivity for behavioral change and restorative justice opportunities. Biophilic design is outlined as a set of principles, attributes and practices for cities to bring nature into urbanites’ daily life. The role of nature in restorative initiatives is traced back to the early work of innovative psychoanalyst, Eric Fromm, illustrating how his framework of human psychological pathways overlaps with biophilic design principles. Together, these approaches should provide new ways to improve the prison experience.